Peripheral thrombosis causing simultaneous saddle pulmonary embolism and paradoxical ST elevation myocardial infarction resulting in cardiovascular collapse. Issue 4 (21st April 2021) - Ghafoor, Hafiz; Sharma, Nitish Kumar; Hashmath, Zeba; Ramsaran, Eddison
Abstract : Paradoxical coronary artery embolism is often an underdiagnosed cause of acute myocardial infarction (MI). It should always be considered in patient with acute MI and a low risk profile for atherosclerotic coronary artery disease. We describe a patient with simultaneous acute saddle pulmonary embolism (PE) and acute ST segment elevation MI due to paradoxical coronary artery embolism. Transoesophageal echocardiography demonstrated a patent foramen ovale with right to left shunt and large saddle PE in the main pulmonary artery and coronary angiography demonstrated acute thrombotic occlusion of the right coronary artery.